2011
DOI: 10.1016/j.ajpath.2011.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Induced by Infection Potentiates Tau Pathological Features in Transgenic Mice

Abstract: Comorbidities that promote the progression of Alzheimer's disease (AD) remain to be uncovered and evaluated in animal models. Because elderly individuals are vulnerable to viral and bacterial infections, these microbial agents may be considered important comorbidities that could potentiate an already existing and tenuous inflammatory condition in the brain, accelerating cognitive decline, particularly if the cellular and molecular mechanisms can be defined. Researchers have recently demonstrated that triggerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
142
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(157 citation statements)
references
References 53 publications
(48 reference statements)
11
142
0
1
Order By: Relevance
“…These changes were associated with increased concentrations of insoluble Ab 1e40 and, albeit to a nonsignificant extent, Ab 1e42 , and increased numbers of Congo redestained Ab-containing plaques in the frontal cortex and hippocampus. Although the factors that initiate inflammation in AD or models of AD are unknown, the present findings suggest that underlying pathology endows a susceptibility to subsequent infection and enhances pathogenic processes; this is broadly consistent with the finding that infection of 3xTg-AD mice with mouse hepatitis virus induced marked tau pathology postinfection (Sy et al, 2011). However Stahl et al (2006) reported that intracerebral infection of Tg2576 mice with the neurotropic Borna disease virus resulted in a decrease in Abcontaining plaques in hippocampus (Stahl et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…These changes were associated with increased concentrations of insoluble Ab 1e40 and, albeit to a nonsignificant extent, Ab 1e42 , and increased numbers of Congo redestained Ab-containing plaques in the frontal cortex and hippocampus. Although the factors that initiate inflammation in AD or models of AD are unknown, the present findings suggest that underlying pathology endows a susceptibility to subsequent infection and enhances pathogenic processes; this is broadly consistent with the finding that infection of 3xTg-AD mice with mouse hepatitis virus induced marked tau pathology postinfection (Sy et al, 2011). However Stahl et al (2006) reported that intracerebral infection of Tg2576 mice with the neurotropic Borna disease virus resulted in a decrease in Abcontaining plaques in hippocampus (Stahl et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…Lipopolysaccharide (LPS)-induced peripheral inflammation exacerbates tau pathology via CDK5-mediated pathway in a transgenic model of AD (Kitazawa et al 2005). Furthermore, a recent study showed that inflammation induced by infection increased GSK3 activity in the triple-transgenic mouse model of AD; this was associated with a shift of tau from the detergent-soluble to the detergent-insoluble fraction (Sy et al 2011). Another study demonstrated detrimental effects of activated microglia in AD (Qiao et al 2001).…”
Section: Microglia In Ad Brainsmentioning
confidence: 97%
“…Similar studies in mice expressing multiple transgenes at low levels are already generating interesting new data and improving available models (see [44] in this issue of Biochemical Society Transactions). Knockin models should also be combined with environmental stresses to better mimic some of the pathogens, toxins and metabolic stress, etc., to which humans are regularly exposed [45].…”
Section: Improving the Accuracy Of Animal Modelsmentioning
confidence: 99%